Geoscientists, Who Have Documented the Rapid and Accelerating Climate Crisis for Decades, Are Now Pleading for Immediate Collective Action. Issue 21 (26th October 2021) - Filippelli, Gabriel; Beal, Lisa; Rajaram, Harihar; AghaKouchak, Amir; Balikhin, Michael A.; Destouni, Georgia; East, Amy; Faccenna, Claudio; Florindo, Fabio; Frost, Carol; Griffies, Stephen; Huber, Matthew; et al.
Key Points: Editors‐in‐chief of AGU journals stress urgent need for greening economy Cross‐sector solutions‐based science must supplement basic research AGU is adding solutions‐based community science journal to portfolio